(untitled) (Research, Society and Development, 2022)
Objective: To report the experience of a university extension project in the realization of health education workshops in a municipal school in the interior of José de Freitas PI. Methodology: This is a descriptive study of the experience report type, carried out from March to August 2018 at the Municipal School Joaquim Euclides da Rocha, located in the Graciosa community, in the interior of the city of José de Freitas PI. The project was composed of academics from the health area, the meetings took place every fortnight with a duration of 2 hours, totaling 12 meetings in all. The activities had the participation of children and adolescents from elementary and high school, in total around 100 children and adolescents participated. Results: The school is a space of great relevance for health promotion, especially when it plays a fundamental role in the formation of critical citizens, stimulating autonomy, the exercise of rights and duties, the control of health conditions and quality of life, with the option of healthier attitudes. The meetings were held through conversation circles, focused on a specific topic each day, always in a playful way, with the intention that the children were interested in participating in the proposed activities. Adolescents were very participatory, questioning and interactive. During the conversation circles, many curiosities and questions were noticed about sexuality, sexually transmitted diseases and reports of a high rate of teenage pregnancy in the community. Conclusion: Health education actions allow a space for exchange between popular knowledge and scientific knowledge, in addition to allowing the construction of a bond between health professionals and users.